2022
DOI: 10.1093/jambio/lxac013
|View full text |Cite
|
Sign up to set email alerts
|

Not just passengers, but co-pilots! Non-rhizobial nodule-associated bacteria promote cowpea growth and symbiosis with (brady)rhizobia

Abstract: Aims To isolate and characterize non-rhizobial nodule-associated bacteria (NAB) from cowpea root-nodules regarding their performance of plant-growth-promoting mechanisms and their ability to enhance cowpea growth and symbiosis when co-inoculated with bradyrhizobia. Methods and Results Sixteen NAB were isolated, identified, and in vitro evaluated for plant growth promotion traits. The ability to promote cowpea growth was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that NAB can affect the number of nodules formed by rhizobia and/or plant growth. In fact, many NAB seem to possess plant-growth promoting traits, making them good candidate as inoculants together with selected rhizobial strains (Martıńez-Hidalgo and Hirsch, 2017;Velaźquez et al, 2017;da Silva et al, 2023). Yet, there is little information currently available on the activity and biological relevance of these NAB within nodules.…”
Section: Direct and Indirect Inter-bacterial Interactions Within Nodulesmentioning
confidence: 99%
“…Numerous studies have shown that NAB can affect the number of nodules formed by rhizobia and/or plant growth. In fact, many NAB seem to possess plant-growth promoting traits, making them good candidate as inoculants together with selected rhizobial strains (Martıńez-Hidalgo and Hirsch, 2017;Velaźquez et al, 2017;da Silva et al, 2023). Yet, there is little information currently available on the activity and biological relevance of these NAB within nodules.…”
Section: Direct and Indirect Inter-bacterial Interactions Within Nodulesmentioning
confidence: 99%
“…Numerous studies have shown that NAB can affect the number of nodules formed by rhizobia and/or plant growth. In fact, many NAB seem to possess plant-growth promoting traits, making them good candidate as inoculants together with selected rhizobial strains ( Martínez-Hidalgo and Hirsch, 2017 ; Velázquez et al., 2017 ; da Silva et al., 2023 ). Yet, there is little information currently available on the activity and biological relevance of these NAB within nodules.…”
Section: Direct and Indirect Inter-bacterial Interactions Within Nodulesmentioning
confidence: 99%